Argument Pedagogy for Everyday Life - Jeffrey P. Mehltretter Drury; Nicholas S. Paliewicz; Sara A. Mehltretter Drury (Central States Communication Association, 2019)
This article assists argumentation and debate instructors in developing courses that provide coverage of foundational concepts while reflecting their own interests. Courses in argumentation and debate also offer instructors an opportunity to teach through applied engagement with contemporary events. We encourage instructors to reflect on the various contexts of argumentation and debate as well as challenging questions concerning the role of technology in the classroom, the conflict between normative and descriptive examples of argumentation, how much to emphasize the role of argumentation and debate in societal change, and the connections between argumentation and deliberation.